DEVELOPING CUSTOMER TRUST THROUGH A COMPREHENSIVE OFFER OF SERVICES: FROM NOTARIES TO INSURANCE - Meri Dilbaryan (Modern American Journals, 2025)
The article examines the concept of a comprehensive service offering that combines notary, insurance and related services into a single ecosystem. The theoretical foundations of trust are analyzed, and its structural elements are highlighted: competence, reliability, transparency and empathy . Based on practical cases, it is shown that this approach increases customer loyalty, reduces transaction costs and promotes long-term cooperation.
Keywords: customer trust, comprehensive service offering, notary services, insurance services, service integration, customer loyalty.